New insight into degradation of chloramphenicol using a nanoporous Pd/Co3O4 cathode: characterization and pathways analysis. (21st May 2022) - Chen, Yiwen; He, Junguo; Jiang, Peigen; Pang, Heliang; Hu, Xuhui; Zhang, Jie; Zhang, Wenjing
Abstract: The growing chloramphenicol (CAP) in wastewater brought a serious threat to the activity of activated sludge and the spread of antibiotics resistance bacteria. In this study, a highly ordered nanoporous Co3 O4 layer on Co foil through anodization was prepared as cathode for nitro-group reduction and electrodeposited with Pd particles for dechlorination to reduce CAP completely. After 3 h treatment, almost 100% of CAP was reduced. Co 2+ ions in Co3 O4 served as catalytic sites for electrons transfer to CAP through a redox circle Co 2+ –Co 3+ –Co 2+, which triggered nitro-group reduction at first. With the presence of Pd particles, more atomic H* were generated for dechlorination, which increased 22% of reduction efficiency after 3 h treatment. Therefore, a better capacity was achieved by Pd/Co3 O4 cathode ( K  = 0.0245 min −1, K is reaction constant) than by other cathodes such as Fe/Co3 O4 ( K  = 0.0182 min −1 ), Cu/Co3 O4 ( K  = 0.0164 min −1 ), and pure Co3 O4 ( K  = 0.0106 min −1 ). From the proposed reaction pathway, the ultimate product was carbonyl-reduced AM (dechlorinated aromatic amine product of CAP) without antibacterial activity, which demonstrated this cathodic technology was a feasible way for wastewater pre-treatment.